2022
DOI: 10.1101/2022.01.12.476009
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Individual variation in dispersal, and its sources, shape the fate of pushed vs. pulled range expansions

Abstract: Ecological and evolutionary dynamics of range expansions are shaped by both dispersal and population growth. Accordingly, density-dependence in either dispersal or growth can determine whether expansions are pulled or pushed, i.e. whether expansion velocities and genetic diversity are mainly driven by recent, low-density edge populations, or by older populations closer to the core. Despite this and despite abundant evidence of dispersal evolution during expansions, the impact of density-dependent dispersal and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 69 publications
(161 reference statements)
0
2
0
Order By: Relevance
“…The maintenance of genetic variance in pushed invasions could therefore also facilitate a weakening of the mechanism on the front. Similarly, studies indicate that positive density-dependent dispersal is expected to be reduced along invasions, by evolving towards density-independent dispersal (Erm and Phillips, 2020;Travis et al, 2009), although recent results suggest that this evolution might not be systematic (Dahirel et al, 2022). Dispersal from the populations behind the front underlying the colonisation debt might therefore also enable the invader to evolve out of the density-dependence mechanisms generating the colonisation debt.…”
Section: Interaction With Genetic Diversitymentioning
confidence: 99%
“…The maintenance of genetic variance in pushed invasions could therefore also facilitate a weakening of the mechanism on the front. Similarly, studies indicate that positive density-dependent dispersal is expected to be reduced along invasions, by evolving towards density-independent dispersal (Erm and Phillips, 2020;Travis et al, 2009), although recent results suggest that this evolution might not be systematic (Dahirel et al, 2022). Dispersal from the populations behind the front underlying the colonisation debt might therefore also enable the invader to evolve out of the density-dependence mechanisms generating the colonisation debt.…”
Section: Interaction With Genetic Diversitymentioning
confidence: 99%
“…In theoretical work, density-dependent dispersal can lead to accelerating range expansions (Travis et al, 2009), due to the evolution of decreased positive density-dependence of dispersal at range fronts. Yet, experimental studies have shown both, reductions (Fronhofer et al, 2017;Dahirel et al, 2021Dahirel et al, , 2022 and increases (Mishra et al, 2020) in positive density-dependence in dispersal during range expansion.…”
Section: Introductionmentioning
confidence: 99%